2008
DOI: 10.1029/2007gl032309
|View full text |Cite
|
Sign up to set email alerts
|

Coseismic and early postseismic slip for the 2003 Tokachi‐oki earthquake sequence inferred from GPS data

Abstract: Early afterslip following the 2003 Tokachi‐oki earthquake is investigated using subdaily GPS time series. Afterslip results are compared with the coseismic slip for the M8 mainshock and the M7.4 aftershock. Afterslip between those two earthquakes is inferred at the southwestern adjacent region of the mainshock, between two epicentral regions, which possibly triggered the aftershock in the southwest. Subsequently, deeper slip occurs. The afterslip loci are distinct from the rupture regions. The non‐uniform prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 26 publications
6
59
1
Order By: Relevance
“…The moment magnitude of the transient is M w ∼ 7.0, but this may be a slight overestimate due to the spatial smoothing inherent in the NSF. The concentration of the transient afterslip in a region downdip of the foreshock's epicenter and peak-slip region is similar to previous observations for the 1994 Sanriku Haruka-oki earthquake (Yagi et al, 2003) which was located just north of the 2011 Tohoku earthquake, and the 2003 Tokachi-oki earthquake (e.g., Miyazaki and Larson, 2008) located further north on the Kurile Trench. Since the maximum of the transient slip distribution is found to be close to the USGS epicenter for the 2011 Tohoku earthquake, it is possible that the foreshock's afterslip promoted the initiation of the mainshock's rupture.…”
Section: Finite Fault Slip Inversionsupporting
confidence: 77%
“…The moment magnitude of the transient is M w ∼ 7.0, but this may be a slight overestimate due to the spatial smoothing inherent in the NSF. The concentration of the transient afterslip in a region downdip of the foreshock's epicenter and peak-slip region is similar to previous observations for the 1994 Sanriku Haruka-oki earthquake (Yagi et al, 2003) which was located just north of the 2011 Tohoku earthquake, and the 2003 Tokachi-oki earthquake (e.g., Miyazaki and Larson, 2008) located further north on the Kurile Trench. Since the maximum of the transient slip distribution is found to be close to the USGS epicenter for the 2011 Tohoku earthquake, it is possible that the foreshock's afterslip promoted the initiation of the mainshock's rupture.…”
Section: Finite Fault Slip Inversionsupporting
confidence: 77%
“…In this study, I have demonstrated that EOF analysis is a powerful tool for enhancing the signal-to-noise ratio of GPS kinematic time series to extract meaningful deformations at the GPS stations. Network Information Filter (NIF) (Segall and Matthews, 1997) can also be used for that purpose, and Miyazaki and Larson (2008) applied it to GPS kinematic time series to infer detailed coseismic slip and subsequent afterslip at the plate boundary. EOF filtering, as used in this study, offers an easy and efficient alternative method to evaluate meaningful slips using GPS kinematic time series that contain large noise.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, GPS kinematic time series are useful. Miyazaki and Larson (2008) fully used the GPS kinematic time series from the Japanese nationwide GPS network (GEONET) to study the 2003 Tokachi-oki earthquake sequence: One of their results was that the afterslip between the mainshock and the M 7.4 aftershock occurred in a region to the southwest of the mainshock, which possibly triggered the aftershock in the southwest. However, identifying the deformation caused by each earthquake and afterslip in the case of the 2011 Tohoku-oki earthquake sequence is a challenging task since the aftershocks and afterslips occurred in a very short time interval after the mainshock.…”
Section: Introductionmentioning
confidence: 99%
“…The static offsets for both the mainshock and aftershock can be used to provide cumulative slip constraints on rupture models (Wald and Graves, 2001). Updated cumulative slip models based on these estimates are available in Miyazaki and Larson (2008).…”
Section: Horizmentioning
confidence: 99%